Spatiotemporal characteristics of ICT use among chinese older adults - Mao Yaqian; Kubo Tomoko (Netcom)
In the landscape of smart city development, older adults in China have often been overlooked due to their limited digital presence and the reliance on big data by city planners. This study addresses this gap by employing a time-geographic diary survey and semi-structured interviews to explore the spatiotemporal dynamics of ICT use among older adults during COVID-19 in Chinese urban context. The findings reveal that while the home remains central to ICT engagement, smartphones introduce hybrid activities that blur the boundaries between leisure and essential tasks. These activities demonstrate older adults' adaptability in balancing offline routines and digital interactions. Government-driven digital initiatives, such as health code systems, accelerated smartphone adoption during the pandemic. However, it was the assistance provided by cross-generational social networks, particularly family members, that played a pivotal role in sustaining older adults’ digital participation. The study also highlights how smartphone use, while enriching older adults' daily lives with increased connectivity and entertainment options, contributes to time fragmentation and new forms of dependency. By leveraging small data, this research sheds light on the overlooked everyday ICT practices of older adults, offering a geographic perspective that underscores their digital vulnerabilities within smart city environments. This study emphasizes that social dynamics, rather than technological infrastructure alone, shape older adults' digital experiences. While the findings are not exhaustive, they suggest practical strategies for policymakers and community organizations to enhance digital inclusion and address the specific challenges encountered by older adults, contributing to more supportive and inclusive smart city ecosystems.